1980
DOI: 10.1002/aic.690260506
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination kinetics of zirconia in an RF chlorine plasma tail flame

Abstract: The chlorination kinetics of zirconia were studied in a single stationary particle reactor system. A plasma of pure chlorine generated by an induction torch provided both the high enthalpy field and the reacting gas. The influence on the rate of conversion of such parameters as temperature, chlorine concentration (in the presence of argon) and particle diameter and porosity were investigated. Based on experimental and theoretical studies, rate equations were developed under different rate controlling mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The fractional order of the reaction found in this study agrees with the order of metal oxide chlorinations reported in the original work by Biceroglu (1978). An order of 0.64 and 1.0 was reported by O'Reilly et a1 (1972) and Landsberg et a1 (1972), respectively, for the chlorination of zirconium dioxide.…”
Section: Influence Of Chlorine Concentrationsupporting
confidence: 92%
See 3 more Smart Citations
“…The fractional order of the reaction found in this study agrees with the order of metal oxide chlorinations reported in the original work by Biceroglu (1978). An order of 0.64 and 1.0 was reported by O'Reilly et a1 (1972) and Landsberg et a1 (1972), respectively, for the chlorination of zirconium dioxide.…”
Section: Influence Of Chlorine Concentrationsupporting
confidence: 92%
“…The kinetic data of these runs are presented in Biceroglu's (1978) previous work. The kinetic data of these runs are presented in Biceroglu's (1978) previous work.…”
Section: Ash Diffusion Versus Pellet Diametermentioning
confidence: 99%
See 2 more Smart Citations
“…The reactor was fabricated from a single piece of Monel (Biceroglu, 1978) and housed a reaction chamber with the crucible containing the residue. Optical pyrometry and spectroscopy measurements were performed through a window in the upper section of the reaction chamber.…”
Section: Introductionmentioning
confidence: 99%